2022
DOI: 10.1177/14680874221125538
|View full text |Cite
|
Sign up to set email alerts
|

A computational assessment of flame speed correlation in an ultra-lean pre-chamber engine

Abstract: Predictive modeling of pre-chamber combustion engines relies primarily on the correct description of laminar and turbulent flame speeds. For engineering applications, the correlations of the flame speeds with physical variables involve empirical constants that are valid for a limited range of operating conditions. The current work aims at assessing the significance of laminar flame speed prediction in the simulation of ultra-lean pre-chamber engine combustion operated with methane. Gülder’s empirical correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Note that the discrepancy between the three cases arises only after the strong jet issuing event ceases and the convective transport of the 𝐺 ̃ field by the jet is minimized so that the effects of turbulent transport and turbulent flame propagation become crucial in determining the overall burning rate. Alkhamis et al [23] demonstrated (not shown here) that by tailoring Gulder's model a perfect match was possible, thus proving the significance of correct laminar flame speed for ultralean PC engine modeling. While ultralean SL measurements with conventional methods are challenging, the ultralean engine data serves as a practical benchmark for the validation of newly developed mechanisms for ultralean engine operation.…”
Section: A Priori Note On Major Modeling Uncertaintiesmentioning
confidence: 56%
See 3 more Smart Citations
“…Note that the discrepancy between the three cases arises only after the strong jet issuing event ceases and the convective transport of the 𝐺 ̃ field by the jet is minimized so that the effects of turbulent transport and turbulent flame propagation become crucial in determining the overall burning rate. Alkhamis et al [23] demonstrated (not shown here) that by tailoring Gulder's model a perfect match was possible, thus proving the significance of correct laminar flame speed for ultralean PC engine modeling. While ultralean SL measurements with conventional methods are challenging, the ultralean engine data serves as a practical benchmark for the validation of newly developed mechanisms for ultralean engine operation.…”
Section: A Priori Note On Major Modeling Uncertaintiesmentioning
confidence: 56%
“…Detailed analysis of jet developments and turbulencechemistry interaction can be found in previous work [21,23]. As the jets are issued into the MC, 𝑢 ′ /𝑆 𝐿 substantially aggrandizes with concomitant decrease in 𝑙 𝑇 /𝛿 𝐿 provided that the region around the jet has significant shear thus smaller turbulent structures.…”
Section: Figure 4: Engine Performance Comparisonmentioning
confidence: 96%
See 2 more Smart Citations